Perspectives on adjunctive use of ketamine for analgosedation during extracorporeal membrane oxygenation. (4th May 2019) - Maybauer, Marc O; Koerner, Michael M; Maybauer, Dirk M
ABSTRACT: Analgosedation on ECMO is more than the choice of any drug, it has to be context specific. Ketamine may be considered as an adjunctive therapy in patients requiring high-dose opioids and sedatives during ECMO support with difficulty to achieve a target RASS. Considering ketamine provides analgesia while maintaining airway reflexes, it could be useful for early ECMO weaning and use of ECMO in awake, non-intubated, spontaneously breathing patients with respiratory failure ('awake' ECMO), especially for patients having considerable waiting periods while being bridged to transplant. The hemodynamic effects of ketamine may provide the benefit of decreasing vasopressor requirements, thereby potentially improving microcirculation. In this context, the effects on end-organ function and the need for renal replacement therapy should be investigated. Pharmacokinetic and pharmacodynamic studies on ketamine ex- and in vivo are of utmost importance to delineate its pharmacological profile and effectiveness during ECMO therapy and to create admissible future study hypothesis.